Novel non‐slip banded balloon catheter for endoscopic papillary balloon dilation in balloon enteroscopy‐assisted endoscopic retrograde cholangiopancreatography. Issue 3 (12th December 2022) - Inoue, Tadahisa; Ibusuki, Mayu; Kutsumi, Hiromu
Abstract : Watch a video of this article.